A panorama of the coverage at the higher educational level for people with disabilities in Mexico - González García, Jonathan Alejandro; Zúñiga Llamas, Alicia; Arce Casas, Pedro Octavio (IE Revista de Investigación Educativa de la REDIECH, 2021)
The research about educational inclusion in Mexico has over poised its “axiological” character to the “facts” issues; that is to say, they have oriented their reflection on how education should be on equal opportunities, instead of what its current situation is. The impact of the actions that have been undertaken, as well as their scope and limitations have been scarcely analyzed. This document analyzes the educational inclusion for people with disabilities at the higher level in Mexico. The focus of the research was mixed, with an exploratory approach. For this task, a performance indicator was developed, whose objective was to measure educational coverage for people with disabilities at this school level. Through the indicator a general diagnosis of inclusion in the various entities of the Republic is offered and at the same time it allows to know the educational gaps. The government programs that have sought to reduce these educational inequalities are also analyzed. In addition, this text aims to contribute to the inclusion agenda for people with disabilities, reports the guidelines on which aspects should be improved, from which national institutions can we learn and how technological tools could contribute to strengthening educational services for this population.